Islamic Work Ethics and Audit Opinions: Audit Professionalism and Dysfunctional Behavior as Intervening Variables - Suryanto, Tulus (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
This study examinesthe relationship between Islamic work ethics and auditors’ opinion, focusing onthe aspects of audit professionalism and dysfunctional behavior as interveningvariables. The research involved in Internal Auditors working of Islamic Bankingindustry in Sumatra Island. A questionnaire was used for data collection. Thestudy represents the empirical test employing census sampling. The data collectedwere analysed using Amos. The results of the study confirmed the three hypothesesexamined: there is a positive corelation between Islamic work ethics and auditors’opinions; auditors’ professionalism is an intervening variable of the correlationbetween Islamic work ethics and auditors’ opinions and dysfunctional behavioris a negative intervening variable of the correlation between Islamic Work Ethicsand auditors’ opinionsDOI: 10.15408/aiq.v8i1.2508